Analysis of the economic value of leaks of personal data - Teppei Koguchi; Toshiya Jitsuzumi; Norihiro Kasuga; Akihiro Nakamura; Manabu Shishikura (International Telecommunications Society (ITS), 2015)
In this research, willingness to pay to prevent a leak of personal data-namely, the person's name, address, email address, and video viewing history-and also the willingness to accept compensation in the event of a leak of this data were estimated using the contingent valuation method. From the results of the estimates, it was found that there were major differences in the willingness to pay and the willingness to accept for leaks of personal data. The willingness to pay was about from 3,100 yen (23 euro) to 3,800 yen (28 euro), while the willingness to accept was about from 14,600 yen (108 euro) to 15,800 yen (117 euro).
Keywords: 330